4
$\begingroup$

Let $(M^n,g)$ be some Riemannian manifold, and let $(x^1,\ldots,x^n)$ be local (oriented) coordinates. Then we may define the Laplace-Beltrami operator $\Delta$ on a function $f\in C^\infty(M)$ by setting $$\Delta f = d^* df = -\operatorname\ast d\operatorname\ast df = -\frac{1}{\sqrt{\det(g_{ij})}}\sum_{j=1}^n\frac{\partial}{\partial x^j}\left(\mathrm{grad}^j\, f\sqrt{\det(g_{ij})}\right)$$ while we can also consider minus the trace of the Hessian, $$ -\operatorname{tr}\operatorname{Hess}(f) = -\operatorname{tr}\nabla^2 f = -g^{ij}\left(\frac{\partial^2 f}{\partial x^i\partial x^j} - \Gamma_{ij}^k\frac{\partial f}{\partial x^k}\right). $$ Now, on flat space, these are exactly identical. But are they the same in general? They both seem to be fairly natural generalizations of the notion of the Laplacian on $\Bbb R^n$.

$\endgroup$
4
$\begingroup$

They are identical. Consider the "divergence formula" used often in Ricci-calculus, given by $$ \nabla_\mu X^\mu=\frac{1}{\sqrt{\det g}}\partial_\mu\left(X^\mu\sqrt{\det(g)}\right). $$

Now let $X^\mu=\nabla^\mu f$. Then we have $$ \nabla_\mu\nabla^\mu f= \frac{1}{\sqrt{\det g}}\partial_\mu\left(\nabla^\mu f\sqrt{\det(g)}\right),$$ which is the trace of the covariant Hessian, and is the same as minus your expression for the Laplace-Beltrami operator.


Edit: About the proof of the divergence formula:

The connection coefficients for the Levi-Civita connection are given by $$ \Gamma^\sigma_{\mu\nu}=\frac{1}{2}g^{\sigma\lambda}(\partial_\mu g_{\nu\lambda}+\partial_\nu g_{\mu\lambda}-\partial_\lambda g_{\mu\nu}). $$

The divergence (with respect to the connection) is given by $$ \nabla_\mu X^\mu=\partial_\mu X^\mu+\Gamma^{\mu}_{\mu\nu}X^\nu, $$ so we need to caclulate the contraction of the connection coefficients:

$$ \Gamma^\mu_{\mu\nu}=\frac{1}{2}g^{\mu\lambda}(\partial_{\mu}g_{\nu\lambda}+\partial_\nu g_{\mu\lambda}-\partial_\lambda g_{\mu\nu}). $$ Due to symmetry, the first and third terms in the brackets cancel, so we're left with $$ \Gamma^\mu_{\mu\nu}=\frac{1}{2}g^{\mu\lambda}\partial_\nu g_{\mu\lambda}. $$

Recall Jacobi's formula (proof is on the wiki page): For a differentiable function $A:\mathbb{R}\rightarrow GL(n,\mathbb{R})$ , we have $$ \frac{d}{dt}\det(A)=\det(A)\text{Tr}\left(A^{-1}\frac{dA}{dt}\right). $$

We apply this formula to the metric tensor with $g=(g_{\mu\nu})$ , so we have $$ \partial_\nu\det(g)=\det(g)\text{Tr}(g^{-1}\partial_\nu g)=\det(g)g^{\mu\lambda}\partial_\nu g_{\mu\lambda}=2\det(g)\Gamma^\mu_{\mu\nu}. $$

We divide by $2\det(g)$: $$ \frac{1}{2}\partial_\nu\ln\det(g)=\Gamma^\mu_{\mu\nu}=\partial_\nu\ln(\sqrt{\det(g)})=\frac{1}{\sqrt{\det(g)}}\partial_\nu\sqrt{\det(g)}. $$

We now insert this expression for the contracted connection coefficients into the expression for the divergence:

$$ \nabla_\mu X^\mu=\partial_\mu X^\mu+\frac{1}{\sqrt{\det(g)}}\partial_\mu\sqrt{\det(g)}X^\mu=\frac{1}{\sqrt{\det(g)}}\left(\sqrt{\det(g)}\partial_\mu X^\mu+\partial_\mu\sqrt{\det(g)}X^\mu\right) \\ =\frac{1}{\sqrt{\det g}}\partial_\mu(\sqrt{\det g}X^\mu).$$

$\endgroup$
  • $\begingroup$ What is the proof of the divergence formula? $\endgroup$ – Monstrous Moonshine Jun 24 '17 at 18:32
  • $\begingroup$ @MonstrousMoonshine Edited post. $\endgroup$ – Bence Racskó Jun 25 '17 at 5:35
3
$\begingroup$

This matter is naturally resolved by using an orthonormal frame, rather than a coordinate frame. To be more precise, let $p\in M$, and let $e_1,\ldots,e_n\in T_pM$ be an orthonormal basis. Extend this basis to a local frame by parallel transport along geodesic rays from $p$. This way, we obtain a local orthonormal frame which satisfies $\nabla e_i|_p=0,\quad i=1,\ldots,n$. Let $\eta^1,\ldots,\eta^n$ denote the dual frame of the cotangent bundle.

Let $f:M\to\mathbb{R}$. Then $df=e_i(f)\eta^i,$ and so, $$*df=(-1)^{i+1}e_i(f)\eta^1\wedge\ldots\widehat{\eta^i}\ldots\wedge\eta^n.$$As each $\eta^i$ satisfies $\nabla\eta^i|_p=0$, we also have $d\eta^i|_p=0$, and so, by the Leibniz rule, we have at $p$ $$d*df=\sum e_i(e_i(f))\eta^1\wedge\ldots\wedge\eta^n=\sum e_i(e_i(f))\mathrm{vol},$$which finally yields$$*d*df|_p=\sum e_i(e_i(f)).$$On the other hand, for the Hessian we have$$\nabla^2f|_p(e_i,e_j)=\nabla_{e_i} df(e_j)=e_i(e_j(f))-df(\nabla_{e_i}e_j)=e_i(e_j(f)),$$or in other words,$$\nabla^2f|_p=e_i(e_j(f))\eta^i\otimes\eta^j.$$The trace is thus equal to $\sum e_i(e_i(f)),$ and we are done.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.